Implementasi Dakwah Muhammadiyah Melalui Kearifan Budaya Lokal dalam Konstruksi Ummatan Wasathon (Studi Dakwah Muhammadiyah di Lampung) - Junaidi Songidan; Nasor Nasor; Marzuki Noor; Fitri Yanti (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This article focuses on research on the implementation of Muhammadiyah da'wah through local cultural wisdom in the 'ummatan wasathon' construction in Lampung. This study uses a qualitative method with a phenomenological and sociological approach to informants taken through purposive sampling with predetermined considerations. Data were collected through interviews, observation and documentation studies. The purpose of this study is to analyze the implementation of Muhammadiyah's da'wah and find out a model of Muhammadiyah's da'wah through local cultural wisdom in the construction of wasathon ummatan. The research findings show that Muhammadiyah's da'wah in implementing the Islamic da'wah movement requires movement reconciliation, through majlis and business charities, so that the da'wah movement can achieve its goals. At the same time, the da'wah is carried out with flexibility and wisdom through local cultural wisdom and becomes a model for the development of Islamic society, namely ummatan wasathon.